Family influence on firm performance: Finnish publicly held family firm perspective. (1st January 2011) - Kansikas, Juha; Tourunen, Kalevi; Laaksonen, Seppo
The study aims at examining the effect of family influence on firm performance. An empirical focus is put on comparison of return on investment of publicly held family and non family firms in Finland. The income statement and balance sheet data of the companies covers the years 2000–2005. The study shows that families are present in 25% of the companies listed on the OMX Helsinki, Finland Stock Exchange. The data indicates that publicly held family firms create close the same value added per employee than non-family firms. According to the results, family firms are less indebted and perform slightly better than non-family firms measured by return on investment. The observations of the study are based on literature review of the family influence on firm performance, descriptive statistics of data and multiple regression analysis.